HAK PILIH ORANG DENGAN GANGGUAN JIWA/INGATAN PASCA PUTUSAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA NOMOR 135/PUU-XIII/2015 - Putri, Delasari Krisda; Achmad, Achmad (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
Democracy as the principle of state administration must be regulated and limited by the constitution. The 1945 Constitution of the Republic of Indonesia has provided guidelines of which is the holding of elections for all Indonesian people, thus as the highest sovereignty of every an Indonesian citizen must have the right to vote in any form without discrimination The problem is that sometimes the administration of the state is often not in accordance with the corridor that has been regulated in the constitution, one of which is the holding of elections which limit the existence of voting rights for people with mental disorders (ODGJ). This is an injury to human rights. The issuance of Constitutional Court Decree Number 135 / Puu-Xiii / 2015 is a change that has a positive impact on the protection of the right to choose people with mental disorders